Organizational strategies for remote learning. Exploratory study during the pandemic at a private university - Ortega Carrillo, Miguel Agustín; Caldera González, Diana del Consuelo (Technium Social Sciences Journal, 2021)
This work explores a model for detecting favorable learning practices among students of the Universidad De La Salle Bajío. It starts with a comparison between classroom teaching style and the style which is being experimented —due to the contingency caused by COVID 19— with technologies for remote classes. From the perception among a group of students of the differences between both models, it is sought to generate strategies from the organizational point of view to create innovative educational content oriented to learning. This is a qualitative investigation, although a subsequent quantitative study of the phenomenon is contemplated. Its scope is correlational: it describes the interrelation between educational practices and organizational strategies. Its documentary design illustrates the importance of the social context as a result of the contingency caused by COVID-19, the use of technologies for remote teaching, and the purpose and interpretation that are built around education from the student’s point of view. For the field research, a workshop was carried out as a pilot test —which is feasible to extend to larger groups— in which the perceptions of a group of six students from different universities and careers about their current learning experience have been collected. The advantages and disadvantages of remote teaching are investigated based on the group’s sense of achievement and the possibilities of systematizing best practices are detailed. The approach is non-experimental and cross-sectional. The sample design is qualitative and not probabilistic. The data obtained in the pilot test allow us to understand in greater depth the characteristics of the educational service —both in person and remotely— from the point of view of the students in two axes. The first is the distinction between educational practices primarily focused on teaching and those primarily focused on learning. The second is the certainty that higher education transforms intuitive knowledge. The main aspects considered for the design of strategies aimed at improving the educational services of a university are described. It also details which are the most appropriate organizational strategies in four aspects: the sustainability of the educational effort, the quality of the education seen as a service, the way in which the organization is configured to strengthen the educational experience and the attention to the personalized experience that each student receives as a beneficiary of an institution.